Milk-sharing experiences: Perspective among Malaysian donors and rexipient mothers - Nurul Akma Jamil; Lee Khuan; Cheong Ai Theng; Siti Mariam Muda (JKP (Jurnal Keperawatan Padjajaran), 2025)
Background: Shared breastmilk has been a longstanding tradition in many cultures throughout history through wet nursing, cross nursing, and the donation of expressed breastmilk to a milk bank. However, social media has introduced some new dynamics to this practice, making it more visible and accessible; and it is known as milk-sharing. Research on milk sharing is still in its infancy and focused on western perspectives. Therefore, the sociocultural dimensions of milk sharing have not been adequately explored across different settings and cultures.